Shopping centers no Brasil: evolução e tendências - Amaral, Manoela Sampaio do (2018)
This study aims to evaluate, under the perception of the executives of the shopping mall market, how is evolution and the trends followed of this equipment, so that they remain active. It is important because it will give clear information about the panorama of the shopping mall sector through experienced and active professionals in the market, which will portray: the sector in general, the market of regulars and important management points to keep them competitive. The research methodology adopted is qualitative, since it is a subject whose result is interpretive, involves values, is restricted to the context, requires authenticity and has the researcher's involvement. Logic is inductive: causality from observations, use of premises, analogies, and generalizations. Observation, analysis, inference, and confirmation / conclusion. The data collection is through face-to-face interviews with executives of shopping centers; the questions where elaborated in an indirect way. These data will be analyzed giving shape to the final conclusion of the work. The main points observed were: the shopping center undergoes a transition. The technology and the consumer’s behavior changes, much has been modified in level of service provision. More ways to buy have been incorporated into the menu of choices of regulars and entertainment has been the main source of attraction. The consumer is diverse. The main threat is obsolescence. The competitor is all that takes the consumer out of the mall. The street shopping and the shopping malls themselves have been timidly quoted. The management of the equipment must be integrative among the component parts of it, and the shopkeeper appears as a partner in the success of the enterprise. The relationship with the shopkeeper takes space and the same level that the entrepreneur. The mall is part of the daily routine of its customers and will remain consolidated, since it quickly adapts the current and future needs of its customers, in terms of convenience, ambience, leisure and entertainment.